Genetic Diversity in Plant Species Characterization and Conservation - El-Esawi, Mohamed A. (IntechOpen, 2019)
Evaluation of the genetic diversity and population structure of plant germplasm enhances breeding and management practices to develop improved varieties. Various genetic tools have been successfully used to study the genetic diversity of plant species, including morphological, cytological, biochemical, and molecular markers. This book discusses the fundamental advances related to assessment, utilization, and conservation of genetic diversity in plant germplasm. The book also discusses approaches related to environmental stresses. Moreover, it sheds new light on the current research trends and future research directions related to plant genetic diversity studies. This book will provoke the interest of various readers, researchers, and scientists, who will find this information useful for the advancement of their plant genetic diversity research work.